OP54 Monitoring Evidence On Overall Survival Benefits Of Anti-Cancer Drugs. (2019) - Grössmann, Nicole; Robausch, Martin; Rosian, Katharina; Wild, Claudia; Simon, Judit
Abstract : Introduction: The introduction of fast-track licensing strategies increases the approval of anti-cancer drugs with ambiguous benefit-risk profiles. Thus, in many instances there is lacking evidence about overall survival (OS) at the time of marketing authorisation. Our objective was to monitor and characterise therapies with ambiguous benefit-risk profiles and identify any post-approval updates on median OS after at least three years of approval by the European Medicines Agency (EMA). Methods: We included all originator anti-cancer drugs with initially ambiguous benefit-risk profiles that received marketing authorization from the EMA between 1 Jan 2009 and 31 May 2015. Our monitoring timeframe was at least three years after EMA-approval. To identify study updates, the following three sources were included: clinicaltrials.gov, European Public Assessment Reports (EPARs), and PubMed. Results: In total, we identified 102 eligible approval studies. Out of these, a negative difference in median OS or no information was available in forty-three (42.2%) instances. During monitoring, eleven updates with accessible information on median OS could be identified. Including monitoring results, there are still thirty-two remaining therapies (31.4%) where no or negative information (n = 27 [26.5%] and n = 5 [4.9%], respectively) regarding median OS was present at least three years after EMA approval. Conclusions: One-third of oncology drugs with ambiguous benefit-risk profiles failed to demonstrate a survival benefit even several years following marketing authorization. Systematic and transparent post-approval monitoring mechanisms will be of high relevance to assure a clinically relevant patient benefit, since the trend towards faster access to medicines with uncertain benefit is increasing rather than declining.